2009
DOI: 10.2223/jped.1879
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and combined risks for anemia in children attending the nurseries of daycare centers

Abstract: Objective: To identify and quantify isolated and combined risk factors for anemia, providing a comprehensive view of the likelihood of its occurrence. Methods:Cross-sectional study with 482 children aged 4 to 29 months attending the nurseries of philanthropic and public daycare centers in the city of São Paulo, Brazil, who participated in two surveys (2004 and 2007). Mothers were interviewed, blood was collected using digital puncture, and anthropometry was performed. Anemia was characterized by hemoglobin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 10 publications
1
14
0
8
Order By: Relevance
“…Greater numbers of children in the household implies more domestic work and worse quality of care for the children, and also means greater demand for foods to supply the needs of all members of the family, which may contribute towards greater risk of anemia. 9,23 In the rural area, the number of children under the age fi ve years in the household did not have any impact on the prevalence of anemia. However, this does not indicate that people living in the rural area had better living conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Greater numbers of children in the household implies more domestic work and worse quality of care for the children, and also means greater demand for foods to supply the needs of all members of the family, which may contribute towards greater risk of anemia. 9,23 In the rural area, the number of children under the age fi ve years in the household did not have any impact on the prevalence of anemia. However, this does not indicate that people living in the rural area had better living conditions.…”
Section: Discussionmentioning
confidence: 90%
“…In the 2006 survey, the variables that showed statistical significance in the final multiple regression model were: child's age; level 1 5 maternal education; level 2 5 environmental index and economic to 67?6 % in Africa, over the period [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005], showing that anaemia is a problem of global nature (1) . In addition to the survey in Pernambuco, other studies conducted in Brazil (2,12) have shown prevalence rates of anaemia above the 29?3 % value estimated by WHO for the Americas (1) . Prevalence rates above 40 % in the country, mainly in children under 2 years of age in rural areas (2,8) , match what WHO states regarding Brazil being among the countries where anaemia is deemed a serious public health problem (1) .…”
Section: Methodsmentioning
confidence: 85%
“…Já a região Nordeste diagnosticou 25,5% das crianças como anêmicas. Resultados superiores ao presente estudo foram encontrados nos estados da Paraíba (19) (25,1%), Minas Gerais (20) (30,6%), Acre (15) (29,2%), Pernambuco (21) (55,6%) e São Paulo (22) (43,6%), para faixa etária semelhante.…”
Section: Discussionunclassified
“…Resultados semelhantes também foram encontrados em outros estudos (29,32) . Em São Paulo, estudo realizado em creches públicas e filantrópicas concluiu que a renda familiar per capita foi uma das variáveis indicadora dos processos estruturais da sociedade que se associou de forma estatisticamente significante com anemia, cujas crianças de família com renda per capita de até 0,5 SM tiveram um risco adicional de 56% de apresentar anemia (22) . Apesar de não ter sido associada à anemia, observou-se no presente estudo que quanto menor a renda, maior foi a prevalência de anemia, constatação essa também relatada em outros estudos (14,30,38) .…”
Section: Discussionunclassified